Safety Climate Survey Among Employees in a Feminine Care Products Manufacturing Company - Annisa, Listia; Lestari, Fatma (Jurnal ilmu kesehatan masyarakat (Online), 2021)
Manufacturing and construction companies are significant contributors to most accidents in Indonesia. Accident frequency rate (AFR) can be reduced by adopting an appropriate management system, technical approach, and safety culture at the workplace. Employees' perception of Work Safety culture is the key to success in minimizing AFR. A survey of employees' perception of safety can identify their reality concerning the Safety Climate at their workplace. The study aimed to observe Safety Climate through a survey of employees' perception on the dimensions of management commitment, safety communication, safety rules and procedures, supportive environment, personal safety involvement and needs, and safety training. The study discusses possible ways to improve the safety climate in their organization and provides feedback to maintain and improve it. A mixed-methods descriptive design was used for this study. The sample size was determined using the Slovin formula and the sample selection using the Proportionate Stratified Random Sampling method. The survey was conducted on 156 employees using a questionnaire model with a personal approach to all levels of employees in a feminine care products manufacturing company. The survey result was analyzed quantitatively through assessments on questionnaires and qualitatively through employees' comments. The study found employees' perception of safety climate to be at a reasonable level. The management commitment dimension in this study has the best assessment result. The analysis results showed that the active role of the leadership, strong safety values to build employee interaction, employee involvement and investment in training programs for employees were critical keys to the successful implementation of Occupational Safety.